A Body Mass Index Measuring Tool with Ultrasonic Sensor and Load Cell (OBEMETER) - rahman, Syaifur; Suryadi, Dedy; Aula, Abqori (Faculty of Engineering, Universitas Tanjungpura, 2025)
Body Mass Index (BMI) is a parameter often used to evaluate the health status based on someone